Genetic relationships and expected responses for genetic improvement of carcass traits of Berkshire pigs - Masamitsu Tomiyama; Takeshi Kanetani; Yuuko Tatsukawa; Hisashi Mori; Takuro Oikawa (Scientia Agricola, 2011)
The Berkshire pig (Sus domestica L.) breed has thin muscle fibers and excellent water-holding capacity. The Berkshire meat makes it widely accepted in the Japanese premium pork market. This study evaluates the accuracy of improving carcass quality with the use of live animal records of Berkshire pigs. Traits analyzed in live animals were: body weight at 60 days of age (W60), age at finish (AGF), daily weight gain from birth to finish (DG), back fat thickness at finish (BFTF), and loin eye area at finish (LEAF), and in carcasses were: carcass weight, loin eye area (LEA), and subcutaneous fat thickness (SCF) at some points, using the records of 4,773 purebred Berkshire pigs. Variance components for the traits were estimated according to the animal model by the Restricted Maximum Likelihood (REML) procedure using the VCE6 program (Neumaier and Groeneveld, 1998). Correlated responses were also calculated. Genetic correlations of back fat thickness (BFT) in live animals with SCF in slaughtered animals were strong, whereas that of LEA between live and slaughtered animals was low. The expected gains by actual selection including W60 and BFTF as selection criterion were superior to other selections. Therefore, selection of live animals at an early stage of growth would be conducive to the production of high quality meat.